2014
DOI: 10.1111/ele.12297
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation tolerance and the loss of avian diversity

Abstract: Urbanisation is considered an important driver of current biodiversity loss, but the underlying causes are not fully understood. It is generally assumed that this loss reflects the fact that most organisms do not tolerate well the environmental alterations associated with urbanisation. Nevertheless, current evidence is inconclusive and the alternative that the biodiversity loss is the result of random mechanisms has never been evaluated. Analysing changes in abundance between urbanised environments and their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
396
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(443 citation statements)
references
References 53 publications
36
396
3
8
Order By: Relevance
“…dietary components, foraging methods and foraging substrates; Table 3). Whilst this finding contrasts with a global comparison in which diet type was not significantly different between urban exploiters and avoiders (Sol et al, 2014), several more local studies have found that urbanized and non-urbanized species differ in their diet or foraging behavior (e.g. Blair, 1996;Kark et al, 2007).…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…dietary components, foraging methods and foraging substrates; Table 3). Whilst this finding contrasts with a global comparison in which diet type was not significantly different between urban exploiters and avoiders (Sol et al, 2014), several more local studies have found that urbanized and non-urbanized species differ in their diet or foraging behavior (e.g. Blair, 1996;Kark et al, 2007).…”
Section: Discussioncontrasting
confidence: 58%
“…Notably, however, when taking into account the number of species within an assemblage, we found consistent evidence across each of our three functional diversity metrics that avian functional diversity is higher in cities than areas of natural habitat. At first sight this seems a remarkable result that is highly unexpected given the plethora of studies showing that urbanization acts as a strong filter of biotic communities favoring species with a particular set of ecological and life history traits (Blair, 1996;Evans et al, 2011;Sol et al, 2014;Fischer et al, 2015) and negative effects of urbanization on avian taxonomic and evolutionary diversity (e.g. Marzluff et al, 2001;Chace and Walsh, 2006;McKinney, 2008;Ibáñez-Álamo et al, 2016) the other two major components of biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that urbanization can act as an ecological filter favoring certain species that are more urban tolerant (Williams et al, 2009;Silva et al, 2016), thus leading to differences in species compositions across urbanization gradients (e.g., for avian communities, Sol et al, 2014;Clucas and Marzluff, 2015). For instance, in such inter-specific context, the "cognitive buffer hypothesis" predicts that larger brained animals have higher adaptive abilities in novel and challenging environmental conditions such as urban habitats (Sol et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While the detrimental effects of urbanisation (e.g., reduced diversity) have been extensively documented for terrestrial (Holway and Suarez 2006;Sol et al 2014;Knop 2016) and lotic systems (Roy et al 2003;Walters et al 2003), ponds have recently been found to follow a different trajectory. Although some studies have reported lower faunal diversity in urban ponds, reflecting management practices for purposes other than biodiversity (Noble and Hassall 2014), others have found urban ponds to support similar faunal diversity to ponds in non-urban settings (Hassall and Anderson 2015;Hill et al 2017a).…”
Section: Introductionmentioning
confidence: 99%